Challenges and opportunities in mixed method data collection on mental health issues of health care workers during COVID-19 pandemic in India - Kulkarni, Ragini; Prusty, Ranjan K.; Chakma, Tapas; Thomas, Beena; Menon, Geetha R.; Singh, Ravinder; Aggarwal, Sumit; Rao, M. V. V.; Periyasamy, Murugesan; Venkateswaran, Chitra; Singh, Prashant K.; Balachandar, Rakesh; et al. (International Journal of Research in Medical Sciences, 2022)
Background: The present paper describes the key challenges and opportunities of mixed method telephonic data collection for mental health research using field notes and the experiences of the investigators in a multicenter study in ten sites of India. The study was conducted in public and private hospitals to understand the mental health status, social stigma and coping strategies of different healthcare personnel during the COVID-19 pandemic in India. Methods: Qualitative and quantitative interviews were conducted telephonically. The experiences of data collection were noted as a field notes/diary by the data collectors and principal investigators. Results: The interviewers reported challenges such as network issues, lack of transfer of visual cues and sensitive content of data. Although the telephonic interviews present various challenges in mixed method data collection, it can be used as an alternative to face-to-face data collection using available technology. Conclusions: It is important that the investigators are well trained keeping these challenges in mind so that their capacity is built to deal with these challenges and good quality data is obtained.